Sound Transmission between Rooms with Curtain Wall Façades: A Case Study. Issue 3 (December 2015) - Secchi, Simone; Cellai, Gianfranco; Fausti, Patrizio; Santoni, Andrea; Martello, Nicolò Zuccherini
Curtain walls have reached good performances in terms of façade sound and thermal insulation, as well as solar protection. Nevertheless, the sound insulation performance of the partition between adjoining rooms with continuous curtain wall façades is often reduced by the presence of direct and flanking transmission through the junction with the façade itself. In this work, flanking and direct structural transmissions are analysed with reference to the joints of the mullion of the curtain wall with lightweight plasterboard partitions. Airborne sound insulation and vibration measurements were made in two adjacent rooms affected by the acoustic problems determined by the curtain wall joint. Traditional acoustic measurements, carried out according to EN ISO 16283–1, highlighted problems in sound insulation between rooms, but without any indication on different sound transmission paths through the wall. Vibration measurements were made for every part of the system (frame columns and beams, window panes, plasterboard wall, plasterboard false ceiling, etc.) to better understand the sound transmission paths in these kinds of structures. In this paper the results of this analysis are presented. Moreover, taking into account previous works and measurements made in this research field, different solutions for curtain wall structures are analysed and technical suggestions are given to improve airborne sound insulation between rooms separated by partitions mounted up to metal frames.